Epochs of Chinese and Japanese art - Fenollosa, Ernest F. (Dover Publications, 1963)
Still regarded as a monumental survey of Eastern art, this comprehensive volume was intended for art collectors and general readers as well as travelers and scholars. It covers China and Korea in addition to Japan, and places a special emphasis on Buddhist influences.